Marx and Freud;Great shakespeareans, Vol.X - Bartolovich,Crystal (Bloomsbury, 2018)
This volume looks at Marx and Freud, who, though not 'Shakespeareans' in the usual academic or theatrical sense, were both deeply informed by Shakespeare's writings, and have both had enormous influence on the understanding and reception of Shakespeare. The first section of this volume consists of a discussion of Marx's use of Shakespeare by Crystal Bartolovich followed by an essay on Shakespeareans' recent uses of Marx by Jean E. Howard. The volume's second half, written by David Hillman, juxtaposes a discussion of Freud's use of Shakespeare with a meditation on Shakespeare's 'use' of Freud. Each part can be read fruitfully independently of the others, but the sum is greater than the parts, offering an engagement with two of the most influential thinkers in Western modernity and their interchanges with, arguably, the most influential figure of early modernity: Shakespeare.